Pengaruh Promosi E-Katalog dan Harga terhadap Keputusan Pembelian melalui Minat Beli di PT. Iwaba Sejahtera Garment - Zakiah, Nani; Maddinsyah, Ali (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
The study aims to determine the effect of E-catalog Promotion and Price on Purchase Interest and its impact on Purchase Decisions. In this research, the researcher used a quantitative approach and survey method. A total of 96 consumers were selected using the Cochran Formula. Data were collected through questionnaires and then processed and analyzed using Path Analysis. The results of the study show: First, E-catalog Promotion and Price have a significant effect on Consumer Purchase Interest simultaneously. Second, E-catalog Promotion has a significant effect on Consumer Purchase Interest partially. Third, Price has a significant effect on Consumer Purchase Interest partially. Fourth, Consumer Purchase Interest has a significant effect on Purchase Decisions. Fifth, E-catalog Promotion and Price have a significant effect on Purchase Decisions through Consumer Purchase Interest simultaneously by. Sixth, E-catalog Promotion has a significant effect on Purchase Decisions through Consumer Purchase Interest. Seventh, Price has an effect on Purchase Decisions through Consumer Purchase Interest partially.